2009
DOI: 10.1177/0731684409341676
|View full text |Cite
|
Sign up to set email alerts
|

Tensile Properties of Copper Core Yarn

Abstract: In this investigation the complex copper core spun yarn (Cotton Sheath and Polyester Sheath) of 179, 118, 98, and 84 tex count of copper core yarns were produced by Dref friction spinning machines and the count of 74 and 59 tex of copper core yarns (cotton sheath and polyester sheath) were produced by ring spinning machines with core attachments device for electromagnetic shielding yarn production purpose. The article reports the effects of the process variables on tensile properties of the copper core yarn as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 6 publications
0
10
0
Order By: Relevance
“…The tensile properties of composite material is playing major role on the application of technical textile in the area of geotextile, industrial textile and automobile textile [2729]. Although many research works have been carried out recently on composite materials, application of sisal and polypropylene blends have not been studied extensively and no exclusive study has been reported in this area of cross direction tensile properties of sisal with polypropylene blended needle punched non-woven fabrics with different blend proportion.…”
Section: Introductionmentioning
confidence: 99%
“…The tensile properties of composite material is playing major role on the application of technical textile in the area of geotextile, industrial textile and automobile textile [2729]. Although many research works have been carried out recently on composite materials, application of sisal and polypropylene blends have not been studied extensively and no exclusive study has been reported in this area of cross direction tensile properties of sisal with polypropylene blended needle punched non-woven fabrics with different blend proportion.…”
Section: Introductionmentioning
confidence: 99%
“…If conductive polymers are applied on the surface of textile material then an electro‐conductive textile composite can be developed, which will be strong, flexible and light‐weight unlike metals. Imparting electrical conductivity to the textile materials by metal coating or incorporating metal wires into textile structure is a common practice . Also, now‐a‐days metal fibers are used during spinning of yarns to make it electro‐conductive .…”
Section: Introductionmentioning
confidence: 99%
“…This can be explained by the amount of yarn used in the fabric structure as well as the placement of the yarns within the multi-axial form. As the openness between the yarns increases, the EMSE of the fabrics decreases [34]. Moreover, it is stated in the literature that the structures with smaller gaps between conductive fibres display higher overall EMSE at high frequencies, on the other hand, bigger gaps between conductive fibres exhibit higher overall EMSE at low frequency [4,35].…”
Section: Emse Performance Of Fabrics and Reinforced Compositesmentioning
confidence: 98%